IXODIDAE TICKS IN KEMEROVO AND THE WAYS OF THEIR ENTRY TO THE CITY TERRITORY: EXPERIENCE OF THEORETIC RESEARCH - Yu. . Kalyagin; K. S. Zubko; G. V. Efremova; Ю. С. Калягин; К. С. Зубко; Галина Викторовна Ефремова (Кемеровский государственный университет, 2010)
There are 11 species of Ixodidae in fauna of Kemerovo region. Most numerous and wide-spread from them are 4 species: Ixodes persulcatus, Ixodes pavlovskyi, Dermacentor pictus and Haemaphysalis concinna. Only 3 species are finds within Kemerovo city boundaries: Ixodes persulcatus, Ixodes pavlovskyi, Dermacentor pictus, where they are constantly brought by pet dogs and also can be brought by mouse-like rodents only in the years of their maximal quantity. A most danger for a man is presented by nymphs, witch can grow up to imago. Фауна иксодид Кемеровской области насчитывает 11 видов. Самыми многочисленными и распространенными являются 4 вида: Ixodes persulcatus, Ixodes pavlovskyi, Dermacentor pictus и Haemaphysalis concinna. В черте города Кемерово встречаются только 3 вида: Ixodes persulcatus, Ixodes pavlovskyi, Dermacentor pictus, куда они постоянно заносятся домашними собаками и могут заноситься мышевидными грызунами только в годы их максимальной численности. Наибольшую опасность для человека в черте города представляют напитавшиеся нимфы, способные линять в имаго.